The Nonvolatile and Volatile Metabolites of Prangos ferulacea and Their Biological Properties - Bruno, Maurizio; Ilardi, Vincenzo; Lupidi, Giulio; Quassinti, Luana; Bramucci, Massimo; Fiorini, Dennis; Venditti, Alessandro; Maggi, Filippo (Planta Medica, 2019)
Prangos ferulacea (L.) Lindl. (Fam. Apiaceae), an orophilous species of eastern Mediterranean and western Asia, possesses a number of biological properties that are worthy of exploitation in different fields. Phytochemical investigations revealed the presence of coumarins, prenyl-coumarins, and furano-coumarins as the main constituents of this species, as well as several flavonoids. Among prenyl-coumarins, osthol is a promising apoptotic agent quite selective toward cancer cells. In addition, the essential oils have been extensively investigated, and several chemotypes have been identified. This work reviews the literature on this species published between 1965 and 2018, describes its volatile and nonvolatile metabolites, and outlines its pharmacological effects.
Keywords: Prangos ferulacea; Apiaceae; coumarins; prenyl-coumarins; furano-coumarins; essential oil